Impact of vitamin B12 on the reproductive health of women with sickle cell disease: a narrative review - Tarimoboere Agbalalah; Faith Owabhel Robert; Emmanuel Amabebe (Bioscientifica, 2023)
Sickle cell disease (SCD) poses an increased risk of infertility, pregnancy complications and maternal and perinatal mortality among women of reproductive age. This risk is particularly higher for women in sub-Saharan Africa, where the disease burden is highest and access to comprehensive health care is limited, as well as in other countries with a high SCD prevalence due to migration. Disease-modifying treatments for SCD could directly and indirectly harm the ovaries, potentially compromising the quality and quantity of existing oocytes. Therefore, it is essential to explore alternative interventions, such as nutritional modifications that are less harmful and cost-effective in order to improve reproductive outcomes and enhance the overall well-being of both mother and child in this population. Maintaining optimal levels of B12 may possibly provide benefits to the ovaries and pregnancy by decreasing homocysteine levels, increasing nitric oxide (NO) bioavailability and promoting antioxidant and anti-inflammatory activities. Individuals living with SCD are more susceptible to vitamin B12 (B12) deficiency. However, there is a lack of clinical data investigating the relationship between systemic levels of B12, its supplementation, and reproductive outcome measures in SCD women. Therefore, this review aims to examine the current evidence regarding the impact of SCD on female reproductive health and the role of B12 in the reproductive biology of women living with SCD.